Intruder detection system for gated community / Syafi Faisal - Faisal, Syafi (2021)
The gated community in neighbourhood is popular choice for people to stay, and it comes with security guards to protect the community. There some problem regarding this security system because security guards only cannot monitor all the houses in the same time and break-ins still happen. The development of an Intruder Detection System for Gated Community is a potential solution for all homeowners in gated communities who want to improve the security of their surroundings. This system is developed in Arduino Uno by using C++ languages and Arduino platform. The main function of this device is it can send a website notification to the security guard and the homeowner and create a short message as a warning and a photo to telegram. If a crime occurs, the security guard can be more focused, and the house owner can be prepared. A security guard can also keep a better eye on the house and its surroundings. When the alarm system is triggered by movement, the homeowner and security guard will receive an alert. Hardware design and software development are the two aspects of this project. The system is built with an ESP32-CAM, Arduino Uno, jumper and PIR sensor. Telegram is utilized in this project to make it more functional, and it is recommended in wireless communication because of its effectiveness and ease of use for sending messages, making calls, and sending pictures. Telegram is utilized due to the growing popularity of mobile phones. The Arduino Compiler is used to program the microcontroller to enable the functions of detecting, tracking, alarm, and alert indicator for detecting theft using a sensor or sending a message to the house owner and security guard.